Effect of Adhesion and Corrosion Performance of Geomet Basecoat (321)-Topcoat (ML Black) Applications on Cataphoretic Coating - Usta, İbrahim; Yılmaz, Oguz; Gül, Minel; Can, Ahmet; Gül, Harun (Sakarya University, 2024)
This study aimed to improve corrosion resistance and adhesion of metallic materials typically used in automotive application. A combination of cataphoretic and Geomet coatings has been used to improve corrosion resistance. Firstly, cataphoretic coating was applied and then the coating process was completed with Geomet 321 and ML Black respectively. The results of the corrosion tests were classified into different categories such as adhesion, water resistance, moisture resistance, salt resistance and cyclic tests. The corrosion properties of the two-and three-layer coatings were found to improve as a function of both the sandblast pre-treatment and the post-cataphoresis curing temperature. The findings show that the adhesion strength and corrosion properties of Geomet 321 increases with curing temperature and sandblasting. This study will be a contribution to the future of protective coatings in the automotive industry by describing the process steps necessary to achieve optimum results. © 2024, Sakarya University. All rights reserved.
Keywords: Cataphoresis; Coating; Corrosion; Geomet; Zinc Lamellar